2015
DOI: 10.1038/npp.2015.339
|View full text |Cite
|
Sign up to set email alerts
|

Autistic-Like Traits and Cerebellar Dysfunction in Purkinje Cell PTEN Knock-Out Mice

Abstract: Autism spectrum disorders (ASDs) are neurodevelopmental disorders characterized by impaired social interaction, isolated areas of interest, and insistence on sameness. Mutations in Phosphatase and tensin homolog missing on chromosome 10 (PTEN) have been reported in individuals with ASDs. Recent evidence highlights a crucial role of the cerebellum in the etiopathogenesis of ASDs. In the present study we analyzed the specific contribution of cerebellar Purkinje cell (PC) PTEN loss to these disorders. Using the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 46 publications
8
108
0
1
Order By: Relevance
“…Previous studies in mouse models have shown that cerebellar dysfunction is sufficient to generate autism-related behaviors in mice 7,23,33,34 but have not examined the specific cerebellar regions responsible for these functions. While differences in RCrusI are strongly associated with ASD, the contribution of RCrusI dysfunction to ASD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in mouse models have shown that cerebellar dysfunction is sufficient to generate autism-related behaviors in mice 7,23,33,34 but have not examined the specific cerebellar regions responsible for these functions. While differences in RCrusI are strongly associated with ASD, the contribution of RCrusI dysfunction to ASD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN was first identified as a tumor suppressor (Li et al, 1997) but later also found to be associated with neurodevelopmental conditions such as epilepsy, macrocephaly, and autism (Goffin et al, 2001; Butler et al, 2005; Buxbaum et al, 2007; Orrico et al, 2009; Varga et al, 2009; McBride et al, 2010; Redfern et al, 2010; Stein et al, 2010; Schaaf et al, 2011; O’Roak et al, 2012b; Busa et al, 2013; De Rubeis et al, 2014; Hobert et al, 2014; Marchese et al, 2014; Vanderver et al, 2014; Codina-Sola et al, 2015; D’Gama et al, 2015; Johnston and Raines, 2015; Krumm et al, 2015; Spinelli et al, 2015; Tammimies et al, 2015; Cupolillo et al, 2016; Schwerd et al, 2016; Tilot et al, 2016). PTEN expression in the brain is positively correlated with the developmental stages of neuronal dendrite formation and synaptogenesis suggesting a role in regulating neuronal function (Perandones et al, 2004).…”
Section: Signaling Molecules Actively Regulate Dendritic Spine and Dementioning
confidence: 99%
“…Knockdown of PTEN in basaolateral amygdala and dentate gyrus, however, does not affect spine density, but spine morphology is dramatically altered with an increase of mature mushroom-shaped spines (Haws et al, 2014). The Pten knockout in cerebellum also results in significant alterations in neuronal morphology of Purkinje cells including swelling of dendrites, and an increase of axonal bouton and dendritic spine size (Cupolillo et al, 2016). The impact of PTEN on spine stability is dependent on the phosphorylation status of its serine/threonin residues and the PDZ-binding motif in its C-terminus (Zhang et al, 2012).…”
Section: Signaling Molecules Actively Regulate Dendritic Spine and Dementioning
confidence: 99%
“…Our behavioral data on autistic-like behaviors in mice with predominant expression of mutant DISC1 in PCs are consistent with those reported for various genetic and environmental models focused on cerebellar pathology and dysfunction, including the maternal immune activation mouse model (Shi et al, 2009; Xu et al, 2013), an early postnatal hypothyroidism rat model (Akaike et al, 1991; Sadamatsu et al, 2006), Staggerer mice (Doulazmi et al, 2001; Goldowitz and Koch, 1986; Herrup and Mullen, 1979; Herrup et al, 1996; Lalonde et al, 1996; Misslin et al, 1986), Shank2 and 3 knockout (KO) mice (Beri et al, 2007; Jiang and Ehlers, 2013; Peca et al, 2011; Peter et al, 2016), Enlarged2 KO mice (Brielmaier et al, 2012; Cheh et al, 2006; Kuemerle et al, 2007; Kuemerle et al, 1997; Millen et al, 1994), Fmr1 KO mice (Ellegood et al, 2010; Koekkoek et al, 2005; Olmos-Serrano et al, 2011; Yuskaitis et al, 2010), and PTEN conditional KO mice (Cupolillo et al, 2016). …”
Section: Discussionmentioning
confidence: 99%